The non-invention of the ceramic arrowhead in world archaeology. (June 2020) - Bebber, Michelle R.; Wilson, Michael; Kramer, Andrew; Meindl, Richard S.; Buchanan, Briggs; Eren, Metin I.
Highlights: Ceramic arrowheads were never invented. This non-invention is puzzling in some ways, expected in others. We experimentally compared ceramic versus flaked stone arrowheads. Ceramic arrowheads possess significant functional limitations. More experimental investigations of "theoretical" artifacts are needed. Abstract: Why, despite over 30, 000 years of ceramic technology and tool diversity documented in the archaeological record – including examples of knapped ceramic scraping tools – was the ceramic arrowhead never invented? Here, we first review the use of ceramic projectile technology and tool use in the archaeological record. Then, via controlled ballistics tests, we investigate whether functional constraints played a role in this global non-invention. By creating "best case" and "worst case" models of ceramic arrowhead, and pitting them both against replica chipped stone counterparts, we show that the former perform significantly worse than the latter in terms of target penetrability and overall durability. By investigating "theoretical" artifacts, we can better understand the evolution of prehistoric technology and why the archaeological record appears the way it does.